Prelamin A impairs 53BP1 nuclear entry by mislocalizing NUP153 and disrupting the Ran gradient. Issue 6 (27th July 2016) - Cobb, Andrew M.; Larrieu, Delphine; Warren, Derek T.; Liu, Yiwen; Srivastava, Sonal; Smith, Andrew J. O.; Bowater, Richard P.; Jackson, Stephen P.; Shanahan, Catherine M.
Summary: The nuclear lamina is essential for the proper structure and organization of the nucleus. Deregulation of A‐type lamins can compromise genomic stability, alter chromatin organization and cause premature vascular aging. Here, we show that accumulation of the lamin A precursor, prelamin A, inhibits 53BP1 recruitment to sites of DNA damage and increases basal levels of DNA damage in aged vascular smooth muscle cells. We identify that this genome instability arises through defective nuclear import of 53BP1 as a consequence of abnormal topological arrangement of nucleoporin NUP153. We show for the first time that this nucleoporin is important for the nuclear localization of Ran and that the deregulated Ran gradient is likely to be compromising the nuclear import of 53BP1. Importantly, many of the defects associated with prelamin A expression were significantly reduced upon treatment with Remodelin, a small molecule recently reported to reverse deficiencies associated with abnormal nuclear lamina.